A responsabilidade enunciativa em textos de um inquérito policial relacionado a crimes de violência contra a mulher - Oliveira, Maria do Socorro (2016)
The object of this investigaton is the enunciative responsibility in police investigation reports related to violent crimes against women. Enunciative Responsibility (ER) is a category of analysis in Texual Discourse Analysis (TDA), which refers to the resources that enunciators use to appropriate language and take up a point of veiw or attribute one to others (cf. ADAM, 2011). The leading questions for this research are: a) how can ER be described linguistically in police investigation reports; b) in what ways do the linguistic marks of ER direct, argumentatively, meaning making in police reports. Given these questions, the general objective of our research is to analyze the linguistic occurrences that indicate ER in police investigation reports. The specific objectives are: to identify occurrences of ER in police reports; analyze the way assuming ER does or does not argumentatively direct the reader to make meanings intended in these texts. We begin with the hypothesis that, assuming ER or not in the texts related to police investigation reports of violent crimes against women, the enunciators (victim, accused, police department official, presiding officer) argumentatively direct their discourse for eliciting the effects of the intended meanings in these texts: be they to accuse, incriminate or defend. The research is generally characterized as textual linguisitics, specifically from the perspective of the TDA, elaborated by Adam (2011), with an emphasis on Enunciation Theory. The methodology can be characterized as qualitative, descriptive documentary research, which investigates a corpus comprised of one police investigation report, collected at a Special Women’s Division of a Police Department. Analytical procedures include the application of eight categories proposed by Adam (2011), which are considered capable of marking the degree of ER of a proposition, revealing: personal marks, spatial and temporal deitics, the verb tenses, modality, the different types of speech, the indications of mediating frames, the autonimic modalization phenomenon, the indication of supporting perceptions and related thoughts. The results show that the linguistic marks of enunciative responsability occur within the utterances, driving the argument to form meanings from the point of view of the various interlocutors (victims, the accused, witnesses, the presiding officer, the police department official), (not) assuming ER argumentatively directs, in the texts analyzed to incriminate or defend the accused. These results reinforce the relevance of the study of the categories that were adopted for this analysis, mainly with respect to the compositional and enunciative aspects of the texts comprising police investigation reports analyzed. The analysis provided a systematic understanding of the function of the categories applied in the texts, referring to their role in the discursive tradition of texts as belonging to the administrative sphere that circulates in the domains of law enforcement and sentencing.